(untitled) (Ameghiniana, 2013)
This work represents the fourth (and last) part concerning the systematic of the paIynomorphs found at Santana Formation.The descriptions of 43 species of pollen-grains, 5 species of incertae sedis spores and 6 species of marine microplankton cysts are here presented.